(untitled) (Islas, 2023)
Introduction: The concept of the non-place, which defines the body through negation, lack, and its depletion, gains full significance in the postmodernist context. In this context, irrationality holds logic, and paradoxes are embraced as natural elements of personal dystopias. Methods: This article explores the main theories of various researchers regarding the body and its categorization as a non-place across different fields of knowledge. Theoretical methods such as historical-logical analysis, analytical-synthetic approaches, and inductive-deductive reasoning are employed. Empirically, text analysis and content analysis are utilized as research methods. Results: This study delves into the theories put forth by scholars associated with structuralism and poststructuralism. It examines how these theories not only consider the body but also encompass the postmodern context. Conclusions: Western society, closely intertwined with the phenomena of speed and spectacle, consistently experiences non-places. Therefore, in recent years, the intellectual sphere has extensively examined the body from various perspectives and configurations. This includes exploring its relationship with identity formation and the frameworks it constructs in both Modernity and Postmodernity.